Otimização e simulação da programação de projetos em estaleiros nacionais considerando restrições de conteúdo local - Fagundes, Raphael Ambrico (2017)
The growth of oil exploration and production in Brazil, especially after the pre-salt oil reserves discovery, implied in ships, rigs and platforms construction demand increase. In this context, the activities planning and scheduling in Brazilian shipyards has become a challenging task to minimize exposure to fines for local content non-compliance clauses and, at the same time, meet the demand of the national oil industry. In order to support the decision-making process of allocating projects to shipyards and dimensioning the exposure to foreign content, this work proposes a mixed integer programming model, based on the classic resource constrained project scheduling problem. Due to the historical delays in the completion of activities by the national shipbuilding industry, a robust model was developed to address the anticipation of possible delays. The parameter known as degree of conservatism was scaled according to the activities lateness probabilities, based on the historical data. Finally, an event discrete simulation model is proposed for sensitivity analysis and delays dimensioning in the projects delivery, and the opportunity cost in the oil production delay.